(untitled) (UNED Research Journal, 2021)
Introduction: There is little ecological information on the grison, Galictis vittata, including its geographic distribution, diet and habitat. Objective: To report the first record of this grison eating a giant toad. Methods: We examined camera trap images from January 2019 to May 2020. Results: We obtained a photo of a grison with a giant toad in its mouth, from an oil palm plantation next to a regenerating forest in Golfo Dulce, Costa Rica, and assumed a successful act of predation. Conclusions: This record represents the first predation event of R. horribilis by G. vittata, as well as the first record of a grison in an oil palm plantation in Costa Rica.